Implementasi Problem Based Learning Berbasis Pendekatan Scientific untuk Meningkatkan Hasil Belajar Matematika - Putri Ayuningtyas; Stefanus Christian Relmasira (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
The aims of this reseacrh was to increased the mathematics learning outcomes through the implementation of scientific approach learning based on problem based learning(PBL) models for the fourth grade students. This research is an action research which consists of two cycles. The data collection used some instruments such as test, observation sheets, and field notes. The subjects of the research were students in 4th grade of SDN Salatiga 03. Data analysis was carried out using comparative descriptive analysis by comparing the results of cycle 1 analysis with the results of cycle 2 analysis. The results showed that the PBL learning model has been shown to increase mathematics learning outcomes for 11,8%, by 67,6% in cycle 1and increased 79,4% in cycle 2. Based on the results of the study, the implementation of scientific approach based on problem based learning (PBL) can increase mathematics learning outcome. Therefore, problem based learning is recommended to be applied in mathematics learning.